QUANTUM FIELD-THEORY ON INCOMPLETE MANIFOLDS - Candelas, P; Raine, D (1976)
A theory of the scalar quantum field on static manifolds is constructed using the language of Feynman Green's functions. By means of examples in which the manifolds are parts of Minkowski space, we show how the "method of images" can be used to solve for the Green's functions. In particular, we consider the Rindler wedge and the space outside a uniformly accelerated conducting sheet. As an example in which the manifold is nonstatic, we consider the region exterior to a conducting sheet which is accelerated impulsively from rest to the speed of light. Finally, we study the steady-state part of de Sitter space where we do not obtain a unique result. Copyright © 1976 American Institute of Physics.